A genetic study of torsion dystonia. Issue 1 (March 1975) - Bundey, S; Harrison, M J; Marsden, C D
Abstract : A family study of 32 patients with torsion dystonia has shown at least two forms of generalized dystonia with onset in childhood. These two forms, an autosomal dominant and an autosomal recessive, are clinically indistinguishable. There were at least three families and probably about six to eight patients with the autosomal recessive variety. The remaining nine to 11 patients with generalized childhood dystonia are thought, because of a probable paternal age effect, to be examples of new dominant mutations. Since fitness with childhood onset is 1/20 of normal, most childhood dominant cases appear sporadically. Most of the other 15 patients (12 with onset in adult life) appear to have a non-genetic torsion dystonia, although an example of a benign adult-onset dominant form associated with a tremor has been observed. It is concluded that there are at least two forms of genetic torsion dystonia, an autosomal recessive form with onset in childhood, which, on evidence from America, is particularly common in Ashkenazi Jews, and one or more dominant forms, with onset in childhood or adult life. The majority of adult-onset isolated cases of idiopathic torsion dystonia seem to be due to exogenous but unidentified causes.